The protective effect of piperine on oxidative stress and hepatic damage induced by diisononyl phthalate in rat. Issue 1 (1st January 2021) - Adeyemo, Oluwatobi Adewumi; Ore, Ayokanmi; Ajisafe, Elizabeth Oyinkansola
ABSTRACT: Diisononyl phthalate (DINP) is a commonly used polyvinyl chloride product in industrial and consumer products with the ability to induce severe hepatotoxicity via oxidative stress. Piperine (PIPE) is an alkaloid from black pepper with proven antioxidant and anti-inflammatory activities. This study investigated whether piperine could promote hepatoprotection against DINP-induced hepatotoxicity in rats. Thirty-two rats were grouped into four treatment groups (n = 8/group): Control, 200 mg/kg/day DINP, 200 mg/kg/d DINP + 60 mg/kg/d PIPE and 60 mg/kg/d PIPE. Oral exposure to DINP induced oxidative damage in the liver via elevated nitric oxide, malondialdehyde, protein carbonyls, as well as depletion of hepatic antioxidants (reduced glutathione, superoxide dismutase, and catalase). These contributed to an increase in plasma levels of liver biomarkers (alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase and total bilirubin) and hepatic histopathological alterations. Our data suggest that PIPE alleviated the oxidative stress, depleted antioxidants, and elevated hepatic function biomarkers induced by DINP.